Enzymatic activity of palmitoyl‐protein thioesterase‐1 in serum from schizophrenia significantly associates with schizophrenia diagnosis scales. Issue 9 (3rd July 2019) - Wu, Yaoyao; Zhang, Qianqian; Qi, Yawei; Gao, Jingjing; Li, Wenqiang; Lv, Luxiang; Chen, Guanjie; Zhang, Zhongjian; Yue, Xuyi; Peng, Shiyong
Abstract: Genome‐wide association studies have confirmed that schizophrenia is an inheritable multiple‐gene mental disorder. Longitudinal studies about depression, first episode psychosis (FEP) and acute psychotic relapse have mostly searched for brain imaging biomarkers and inflammatory markers from the blood. However, to the best of our knowledge, the association between enzymatic activities with diagnosis or prediction of treatment response in people with schizophrenia has barely been validated. Under the Longitudinal Study of National Mental Health Work Plan (2015‐2020), we have studied a subsample of approximately 36 individuals from the cohort with data on palmitoyl‐protein thioesterase‐1 enzymatic activity from FEP and performed a bivariate correlation analysis with psychiatric assessment scores. After adjusting for sex, age, body mass index (BMI) and total serum protein, our data demonstrated that PPT1 enzymatic activity is significantly associated with schizophrenia and its Positive and Negative Syndrome Scale (PANSS) scores. This longitudinal study compared the PPT1 enzymatic activity in FEP schizophrenia patients and healthy volunteers, and the former exhibited a significant 1.5‐fold increase in PPT1 enzymatic levels (1.79 mmol/L/h/mL, and 1.18 mmol/L/h/mL; P  < 0.05; 95% CI, 2.3‐2.9 and 1.4‐1.8). The higher PPT1 enzymatic levels in FEP schizophrenia patients were positively associated with larger PANSS scaling scores ( r  = 0.32, P  = 0.0079 for positive scaling; r  = 0.41, P  = 0.0006 for negative scaling; r  = 0.45, P  = 0.0001 for general scaling; and r  = 0.34, P  = 0.0048 for PNASS‐S scaling). Higher enzymatic PPT1 in FEP schizophrenia patients is significantly associated with increased PANSS scaling values, indicating more serious rates of developing psychosis. Enzymatic activity of PPT1 may provide an important new view for schizophrenia disorders.